Séries múltiplas de squat jump aumentam o salto vertical de saltadores de elite no atletismo? - Moura, T. A.; Oliveira, L. S.; Ricardo, R. F.; Costa, M. A.; Okazaki, V. H. A. (Revista Brasileira de Ciência e Movimento, 2018)
Strength exercises as conditioning activity can result in improvement of muscle contraction process and performance of athletes in the subsequent activity. However, little is known about the eff ect of a specific conditioning activity of the elite athletes` training routine on their subsequent performance. Thus, this study analyzed the eff ect of two conditioning activities on the vertical jump (VJ) height in athletes of jump events in elite athletics (track and fi eld): Squat Jump (SJ) and Drop Jump (DJ). Twelve elite athletes [7 men; Mean (SD), age: 24 (5) years; body mass: 84.4 (7.5) kg; height: 1.86 (0.06) m and 5 women; age: 25 (5) years; body mass: 59.0 (3.1) kg; height: 1.72 (0.06) m] participated in a crossover study. Athletes performed a countermovement VJ test adapted from Abalakow after three randomized conditions: control (no conditioning activity), 3 x 3 SJ with 80% body mass and 3 x 10 DJ at a height of 40 cm. A 3-min interval was adopted among conditions and a 1-min interval was adopted among VJ trials. Athletes demonstrated higher height after SJ [Mean (SD) = 52.0 (4.8) cm] compared to control condition [Mean (SD) = 49.1 (4.2) cm], P = 0.027, d = 0.63, however, this difference was not seem relevant. SV performance seems to be infl uenced by the number of jumps, which was higher when compared to other studies. Therefore, athletes of modalities for power in the lower extremity in athletics may benefi t only partially from the eff ects of SJ in improving their VJ performance.